WANPRESTASI DALAM PERJANJIAN KERJA SAMA PEMBERIAN KREDIT MODAL KERJA ANTARA PT. BANK RAKYAT INDONESIA DAN CHARLES FOEK: Studi Putusan N : 13/PDT.G/2011/PN.END. dan Kasasi No. 2519 K/PDT/2013 - Qiram, Syahrul; Taufik, Moh (LPPM Universitas Bina Bangsa, 2024)
Agreements made legally validas the law of the perties who made it. This means that the agreements is valid and legally bindingon the parties. For businesses, the agreement a major foundation that serves as a gide or handle in meeting achievement and dispute resolution in the event of a dispute in the future. One of the cooperation agreement can be seen between the store PT. Bank Rakyat Indonesia and Charles Foek. The problems became the main object of this research is on the implementation of cooperation agreements and the obstacles encountered in the process of development effort under taken. The purpose of this study was to determine the cooperation agreements and the store PT. Bank Rakyat Indonesia and Charles Foek about the glass ware in Ende Tengah, sub-district, district Ende NTT, whe ther the constraints faced by the parties in developing a business venture under taken now. This study use empirical method using primary data and secondary data were then analyzed using a qualitative approach. Cooperation agreement between the store PT. Bank Rakyat Indonesia and Charles Foek aim are hidden defects or “wanprestasi”. From the results of the discussion can make a conclusion that the contract should be more careful in making the agreement as well a sist aims and objectives